Application of Some Selected Plants Biomasses in Treatment of Wastewater - Jabir Danyaya Aliyu; Ibrahim Abubakar; Sani Maliki; Siddiku Gwadangaji Umar (Biology, Medicine, & Natural Product Chemistry, 2026)
Wastewater contains several different hazardous substances and its consumption causes various diseases. Different plants biomasses have phytoremediation potential with significant application in wastewater treatment. The heavy metals contents of the treated and untreated wastewater sample were estimated using atomic absorption spectroscopic method. The physicochemical properties of the treated and untreated wastewater sample were determined using standard equipment and analytical methods. The total and faecal coliforms count was performed using membrane filtration method. In comparison, with the untreated wastewater, T. domingensis and P. glaucifolium exhibited significant (p < 0.05) decrease in pH, turbidity, conductivity, total hardness (TH), total suspended solids (TSS), total dissolved solid (TDS), biological oxygen demand (BOD), chemical oxygen demand (COD), total alkalinity (TA), chloride, sulphate, phosphate, and nitrate level in the wastewater sample with high percentage removal of the physicochemical contaminants. The wastewater sample treated with T. domingensis and P. glaucifolium displayed significant (p < 0.05) reduction in the level of Ni, Mn, Cr, Pb, Cd, and Co in the wastewater sample compared with the untreated sample. the coliforms load in the wastewater sample. The total and faecal coliforms load in the wastewater sample treated with T. domingensis and P. glaucifolium was significantly (p < 0.05) reduced compared with the untreated wastewater sample. The Typha domingensis demonstrated high significant (p < 0.05) removal efficiency against the physicochemical contaminants, heavy metals, andtotal and faecal coliforms population in the wastewater compared to the Pennisetum glaucifolium.